Design and Development of Product Sales Website Using the Waterfall Methodology: An Academic Approach - Megananda, Evelyn Gina; Khairunisa, Fitria Is’aaf; Fadillah, Septiya Nur; Ali, Siti Saekhah; Tarwoto (International Journal for Applied Information Management, 2023)
The development of digital technology and the internet has significantly changed the business landscape, especially in terms of product marketing and promotion. One area that has been significantly affected is the MSME (Micro, Small, and Medium Enterprises) industry. MSMEs often face challenges in expanding their market and increasing their revenue due to limited resources and limited accessibility. The existence of a website can make it easier for business actors to promote their products in order to reach wider marketing and make it easier and faster for consumers to find product information provided by business owners. The purpose of this research is to create a marketing website using a Waterfall with the help of WordPress software.